Meiotic Cohesin and Variants Associated With Human Reproductive Aging and Disease - Beverley, Rachel; Snook, Meredith L.; Brieño-Enríquez, Miguel Angel (Frontiers in Cell and Developmental Biology, 2021)
Successful human reproduction relies on the well-orchestrated development of competent gametes through the process of meiosis. The loading of cohesin, a multi-protein complex, is a key event in the initiation of mammalian meiosis. Establishment of sister chromatid cohesion via cohesin rings is essential for ensuring homologous recombination-mediated DNA repair and future proper chromosome segregation. Cohesin proteins loaded during female fetal life are not replenished over time, and therefore are a potential etiology of age-related aneuploidy in oocytes resulting in decreased fecundity and increased infertility and miscarriage rates with advancing maternal age. Herein, we provide a brief overview of meiotic cohesin and summarize the human genetic studies which have identified genetic variants of cohesin proteins and the associated reproductive phenotypes including primary ovarian insufficiency, trisomy in offspring, and non-obstructive azoospermia. The association of cohesion defects with cancer predisposition and potential impact on aging are also described. Expansion of genetic testing within clinical medicine, with a focus on cohesin protein-related genes, may provide additional insight to previously unknown etiologies of disorders contributing to gamete exhaustion in females, and infertility and reproductive aging in both men and women.